S100A11 Promotes Acute Pancreatitis by Upregulating Acinar Cell Ferroptosis - Huiyun Zhu; Hongxin Sun; Xianzhu Zhou; Ge Li; Yun Zhang; Youhan Zhang; Jia Gui; Siying Fei; Xiaoyang Dong; Xiaoju Su; Yan Chen; Cui Chen; et al. (Mediators of Inflammation)
Acute pancreatitis (AP) is a common gastrointestinal disease that can cause systemic inflammation and lead to dysfunction of multiple organs. In pancreatitis, ferroptosis promotes disease progression and organ damage by regulating oxidative stress and inflammatory response. Here, ferroptosis was significantly elevated in the AP rat model and participated in regulating disease progression. Meanwhile, the expression of S100A11 was significantly upregulated in the pancreatic tissue of rats with AP, as determined by tandem mass spectrometry (TMT) proteomics. This phenomenon was also confirmed in pancreatic acinar cells. To reveal whether S100A11 participates in regulating ferroptosis, an S100A11 knockdown lentivirus was transfected into caerulein-treated pancreatic acinar cells AR42J. Functional results revealed that S100A11 knockdown significantly increased cell viability and GSH levels, while decreasing reactive oxygen species (ROS), lipid ROS, and Fe2+ levels in pancreatic acinar cells compared to the control group. In vivo, S100A11 knockdown via adeno-associated virus inhibited caerulein-induced ferroptosis. These findings suggest that S100A11 promotes AP by upregulating ferroptosis, which exacerbates oxidative stress and inflammation in pancreatic tissue.